PkM Pelatihan Skrining Orang Dengan Gangguan Jiwa (ODGJ) - Mamnuah Mamnuah; Dwi Ernawati; Triyono Triyono (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The high incidence of schizophrenia in the Kasihan I Community Health Center (Puskesmas) area (107 residents) necessitates greater adres understanding of how to screen for and assess the stability of people with mental disorders, which is currently still limited. This activity aims to improve the knowledge of mental health cadres regarding schizophrenia and the use of instruments for early detection of mental health problems. The activity began with a Focus Group Discussion (FGD) and was followed by training for 32 mental health cadres. Participants’ understanding was assessed using pre-test and post-test instruments. There was a significant increase in knowledge, with the average pre-test score of 68.75 rising to 84.68 on the post-test. The group of homemakers showed the highest score increase, while the group with an educational background experienced a ceiling effect. Community-based screening training is highly effective in improving mental health literacy. For future training, it is recommended to use visual and interactive methods (role-playing) to accommodate participants with a basic education background.